Human biochemistry - Litwack, Gerald (San Diego, CA, United States : Elsevier, 2022)
"Presents an update on a past edition winner of the 2018 Most Promising New Textbook (College) Award (Texty) from the Textbook and Academic Authors Association and the PROSE Award of the Association of American Publishers Provides a fully updated resource on current research in human and medical biochemistry Includes clinical case studies, applications, chapter summaries and review-based questions Adopts a practice-based approach, reflecting the needs of both researchers and clinically oriented readers"--
Organ systems and tissues -- The cell -- Water, pH, buffers, general features of receptors, channels and pumps -- Proteins -- Enzymes -- Insulin and sugars -- Glycogen and glycogenolysis -- Glycolysis and gluconeogensis -- Lipids -- Nucleic acids and molecular genetics -- Protein biosynthesis -- Transcription -- Metabolism of amino acids -- Metabolism of fat, carbohydrate and nucleic acids -- Polypeptide hormones -- Steroid hormones -- Growth factors and cytokines -- Membrane transport -- Micronutrients (metals and iodine) -- Vitamins and nutrition -- Blood and lymphatic system.
Includes bibliographical references and index.
Keywords: Clinical biochemistry; Biochemical Phenomena; Biological Phenomena; Metabolism; Clinical Medicine; Clinical biochemistry